Lack of an Effect of Supratherapeutic Dose of Venlafaxine on Cardiac Repolarization in Healthy Subjects. Issue 1 (9th July 2021) - Abbas, Richat; Riley, Steve; Nepal, Sunil; Bachinsky, Mary; Lee, Kimberly C.; Chappell, Phillip B.; Damle, Bharat
Abstract: This single‐center, randomized, 3‐way crossover thorough QT study evaluated the effect of steady‐state supratherapeutic venlafaxine (Effexor) on cardiac repolarization. Fifty‐four healthy adults received double‐blinded extended‐release venlafaxine 450 mg/d and placebo and open‐label positive‐control moxifloxacin 400 mg. The postdose QT intervals corrected for heart rate using the Fridericia formula (QTcF) were assessed on day 14 with an analysis of covariance using a mixed‐effects model. At each time, the upper bound of the 2‐sided 90%CI for time‐matched least‐squares (LS) mean difference between venlafaxine and placebo did not exceed the predefined cutoff of 10 milliseconds; the highest 90%CI upper bound was 5.8 milliseconds 24 hours postdose, demonstrating the lack of effect of venlafaxine on the QTc interval (primary objective). Assay sensitivity was established because the lower bound of the 2‐sided 90%CI for LS mean difference in QTcF between moxifloxacin and placebo was 7.413 milliseconds on day 14 (postdose 3 hours). The exposure‐response analysis demonstrated no evidence of increase in QTcF with increase in venlafaxine and desvenlafaxine concentrations. Also, supratherapeutic venlafaxine was found to be safe and well tolerated. Overall, the results demonstrated the lack of significant prolongation of the QTc interval with supratherapeutic venlafaxine 450 mg/d.